Time-varying uncertainty and the credit channel - Kevin D. Salyer; Victor Dorofeenko; Gabriel Lee (University of California, Department of Economics, 2005)
We extend the Carlstrom and Fuerst (1997) agency cost model of business cycles by including time varying uncertainty in the technology shocks that affect capital production. We first demonstrate that standard linearization methods can be used to solve the model yet second moments enter the economy's equilibrium policy functions. We then demonstrate that an increase in uncertainty causes, ceteris paribus, a fall in investment supply. A second key result is that time varying uncertainty results in countercyclical bankruptcy rates - a finding which is consistent with the data and opposite the result in Carlstrom and Fuerst. Third, we show that persistence of uncertainty affects both quantitatively and qualitatively the behavior of the economy. However, the shocks to uncertainty imply a quantitatively small role for uncertainty over the business cycle.
Keywords: E20; E40; E50; 330